2019
DOI: 10.1139/apnm-2018-0101
|View full text |Cite
|
Sign up to set email alerts
|

Microneurographic characterization of sympathetic responses during 1-leg exercise in young and middle-aged humans

Abstract: Muscle sympathetic nerve activity (MSNA) at rest increases with age. However, the influence of age on MSNA recorded during dynamic leg exercise is unknown. We tested the hypothesis that aging attenuates the sympatho-inhibitory response observed in young subjects performing mild to moderate 1-leg cycling. After pre-determining peak oxygen uptake (VO2peak), we compared contra-lateral fibular nerve MSNA during 2 minutes each of mild (unloaded) and moderate (30-40% of the work rate at peak VO2, halved for single l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 44 publications
(63 reference statements)
0
26
0
Order By: Relevance
“…The purpose of their recruitment was to determine how closely sympathetic responses of trained HFrEF patients approximated those of middle-aged healthy subjects. Although the mean age of the control group was slightly lower than that of participants with HFrEF, in healthy subjects age does not affect the MSNA burst frequency response to exercise at these intensities (36).…”
Section: Limitationsmentioning
confidence: 67%
“…The purpose of their recruitment was to determine how closely sympathetic responses of trained HFrEF patients approximated those of middle-aged healthy subjects. Although the mean age of the control group was slightly lower than that of participants with HFrEF, in healthy subjects age does not affect the MSNA burst frequency response to exercise at these intensities (36).…”
Section: Limitationsmentioning
confidence: 67%
“…) and single‐leg exercise (Notarius et al . ), which may have augmented the reductions in pressure for these patients following ET A receptor antagonism. Based on the current reductions in leg MAP, systemic diastolic blood pressure and concomitant central cardiovascular responses (increase in heart rate, stroke volume and cardiac output) in the present investigation, we speculate that acutely administered ET A receptor antagonism in both legs or systemically during a whole body exercise modality, where such central cardiovascular responses are more limited, may deleteriously lower systemic MAP in hypertensive individuals.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies measured MSNA during head-down tilt and lower body negative pressure in elderly individuals and found that cardiopulmonary baroreflex control of sympathetic vasomotor outflow is not impaired with age in healthy humans Tanaka et al, 1999). To the best of our knowledge, no study has examined the effect of age on MSNA during dynamic exercise, except that of Notarius et al (2019); they found similar reductions in MSNA burst frequency (BF) during mild one-legged cycling between young (23 ± 1 years) and middle-aged (57 ± 2 years) healthy subjects. Thus, muscle pump-induced inhibition of sympathetic vasomotor outflow (i.e., cardiopulmonary baroreflex) during low-intensity exercise is apparently preserved in middle-aged individuals.…”
mentioning
confidence: 99%
“…Thus, muscle pump-induced inhibition of sympathetic vasomotor outflow (i.e., cardiopulmonary baroreflex) during low-intensity exercise is apparently preserved in middle-aged individuals. However, muscle pumping may be reduced in older subjects (Notarius et al, 2019;Proctor & Parker, 2006) because of a decrease in limb muscle mass (Frontera et al, 2000) and/or changes in venous compliance (Olsen & Lanne, 1998) with advancing age. Notarius et al (2019) did not estimate variables associated with the muscle pump-induced increase in venous return (e.g., a change in central venous pressure; CVP) that loads cardiopulmonary baroreceptors during cycling.…”
mentioning
confidence: 99%
See 1 more Smart Citation